Effect of percutaneous coronary intervention on global hemodynamics and the prevalence of residual microvascular dysfunction. (22nd December 2021) - Misawa, Toru; Kanaji, Yoshihisa; Sugiyama, Tomoyo; Hoshino, Masahiro; Yamaguchi, Masao; Hada, Masahiro; Nagamine, Tatsuhiro; Teng, Yun; Nogami, Kai; Ueno, Hiroki; Yasui, Yumi; Sayama, Kodai; et al.
Abstract: Objectives: We aimed to examine the changes in hyperemic coronary sinus flow (CSF) and global coronary flow reserve (g‐CFR) after percutaneous coronary intervention (PCI) and investigate the predictors to improve these metrics and the prevalence of residual coronary microvascular dysfunction (CMD). Methods: This prospective, single‐center study included 118 patients with stable coronary artery disease undergoing PCI for a single proximal lesion. Phase‐contrast cine‐cardiac magnetic resonance (PC‐CMR) was used to assess hyperemic CSF (HCSF) and g‐CFR, before and after PCI. Residual CMD was defined as concordantly impaired post‐PCI HCSF (<2.3 ml/min/g) and g‐CFR (<2.0). Results: HCSF significantly increased, although 38 (32.2%) patients showed a decrease. There was no significant change in g‐CFR despite fractional flow reserve (FFR) improvement in all target territories. Concordantly increased HCSF and g‐CFR were effectively discriminated by adding PC‐CMR‐derived information to pre‐PCI FFR. Residual CMD was observed in 30 (25.4%) patients and was associated with pre‐PCI renal dysfunction and lower pre‐PCI rest and hyperemic CSF, but not with pre‐PCI regional physiological indices. Conclusions: FFR‐guided PCI was associated with increased HCSF, but not with increased g‐CFR. After uncomplicated PCI, one‐quarter of patients showed residual CMD. Our approach may help identify patients who may benefit from increased coronary perfusion or show residual CMD.